ELEMENTS OF SHAKESPEAREAN TRAGEDY IN COMIC SERIES “DEATH NOTE” - Lika Silvia Batubara (Adisam Publisher, 2024)
Death Note is one of popular manga (comic) and anime series in Japan. This comic series was created by Tsugumi Ohba and Takeshi Obata. The main character, Light Yagami, is a high school student who discovers a black supernatural notebook. It simply titled “Death Note”. The death note grants user the ability to kill someone with the knowledge of the victim’s name and face by writing the victim's name while remembering his or her face. The series centers around Light Yagami’s attempt to create and rule a world “cleansed of evil” as a “God” using the death note. Death Note is full of symbolism from Roman overtones to literary masterpieces (Machbeth, Hamlet and Othello). Same with Macbeth, Light Yagami’s tragic flaw is also caused by his obsession with power. The power of the death note awakens great ambisions and leads him to murder and insanity protect what he has claimed. He should face a horrible death that is fitting to the way he lives. This is the basic premise of William Shakespeare’s tragedy and it is also the heart of Death Note. Furthermore, the main aim of this paper was to acknowledge to the readers the elements of Shakespearean tragedy in the anime Death Note.